BENEFITS OF USING DIGITAL LEARNING PLATFORMS FOR STUDENTS AND TEACHERS: BENEFITS OF USING DIGITAL LEARNING PLATFORMS FOR STUDENTS AND TEACHERS - Koyshekenova, Tatyana; Tulesinova, M (Журнал иностранных языков и лингвистики, 2025)
In the ever-evolving landscape of education, digital learning has emerged as a game-changer, offering a plethora of benefits for both students and teachers. This dynamic shift from traditional classrooms to virtual learning environments brings with it a host of advantages, fostering a more flexible, personalized, and engaging educational experience.